2010
DOI: 10.1590/s1980-65232010000400002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the maternal's periodontal status on the detection of periodontal pathogens in newborn children

Abstract: Purpose: To evaluate the influence of the mother's periodontal clinical status on the prevalence of periodontal pathogens in newborns. Methods: Seventy-six pairs of newborns and their biological mothers were selected. After a periodontal examination, the mother-child pairs were divided into two groups according to their maternal periodontal clinical status: mothers with (Group A, n=33) or without periodontitis (Group B, n=43). The oral colonization of newborns by five periodontopathogens (A. actinomycetemcomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…P. gingivalis detection rates was estimated at 68.8% in children. A study evaluating the influence of mother's periodontal clinical status on the prevalence of periodontal pathogens in newborns (aged of 3 months) showed that P. gingivalis was the most prevalent pathogen followed by others periodontal bacteria (Prevotella intermedia, Tannerella forshythia, Campylobacter rectus, Aggregatibacter actinomycetemcomitans) [37]. They concluded that the maternal clinical periodontal status is a significant indicator of the oral microbiota composition in the newborn children.…”
Section: Clinical Implications Of Familial Porphyromonas Gingivalis Smentioning
confidence: 99%
“…P. gingivalis detection rates was estimated at 68.8% in children. A study evaluating the influence of mother's periodontal clinical status on the prevalence of periodontal pathogens in newborns (aged of 3 months) showed that P. gingivalis was the most prevalent pathogen followed by others periodontal bacteria (Prevotella intermedia, Tannerella forshythia, Campylobacter rectus, Aggregatibacter actinomycetemcomitans) [37]. They concluded that the maternal clinical periodontal status is a significant indicator of the oral microbiota composition in the newborn children.…”
Section: Clinical Implications Of Familial Porphyromonas Gingivalis Smentioning
confidence: 99%